Developing offshore outsourcing practices in a global selective outsourcing environment – the IT supplier’s viewpoint - Majanoja, Anne-Maarit (2022)
Currently, internal IT organizations use outsourcing and offshore arrangements to achieve cost savings and gain access to new capabilities. It was found that suppliers’ personnel at the operational level can face challenges with internalizing their operations based on the agreed outsourcing practices and transferred responsibilities. This study gives voice to the supplier and studies the impact of offshore outsourcing operation development activities. The internal IT unit from Nokia Devices selectively outsourced global IT service activities and responsibilities to the IT supplier. The outsourced activities were implemented by offshore centers in India and China. It was found that the global selective outsourcing environment (GSOE) did not provide a solution to all of their expectations, and new unexpected challenges occurred. Several practices, communication and information sharing, and behavior-related lessons learned items were identified. It was found that the GSOE operation needs to be developed and implemented in an agile and incremental manner, instead of a singular implementation approach. Also, the globally distributed teams’ group dynamics critically impacted on the teams’ ability to work. The lessons learned items and recommendations can be utilized by other companies during their mode-of-operation development.